Enhancement of perceived body ownership in virtual reality-based teleoperation may backfire in the execution of high-risk tasks. (February 2021) - Shin, Mincheol; Lee, Sanguk; Song, Stephen W.; Chung, Donghun
Abstract: Guided by previous research on the role of embodiment in virtual environments, this study aimed to investigate the potential effects of using human-like (compared to robotic) virtual hands on work performances in the context of virtual reality (VR)-based teleoperation of high-risk machinery. A 2 × 2 mixed factorial design experiment ( N  = 74), with the virtual hand representation as a within-subjects factor (robotic vs. human-like virtual hands) and the risk of danger as a between-subjects factor (low vs. high), was conducted to examine the effects of virtual hand representations (i.e., human-likeness) on perceived body ownership (i.e., embodiment), risk perception, intention to work using the teleoperator, and work performance (i.e., the number of successful task completions). In addition, the moderating effects of the risk of danger on the relationship between perceived body ownership and risk perception were explored. Results showed that the enhancement of perceived body ownership in VR-based teleoperation, induced by the use of human-like hands, increased the risk perception and degraded workers' task performances in the execution of high-risk tasks. Further implications of the findings were discussed. Highlights: The use of human-like virtual hands in VR-based teleoperation enhanced perceived body ownership (PBO). PBO increased the risk perception (RP) in the execution of high-risk tasks. RP negatively influenced work performances. RP negatively influenced intention to work using the VR-based teleoperator.